Microbiological evaluation of grated coconut (Cocos nucifera) sold in open markets in the municipality of Belém, Pará State, Brazil - Abreu, Marta Gorett Guilhermina de (2019)
OBJECTIVE: To carry out the microbiological evaluation of grated coconut (Cocos nucifera) in natura sold in three open markets in the municipality of Belém, Pará State, Brazil. MATERIALS AND METHODS: Samples were collected in two periods of the day, for a total of 18 ones, which were evaluated by the most probable number method for total and thermotolerant coliforms and conventional methods for Salmonella sp. RESULTS: Coliforms were detected in all samples, however those obtained in the first period were considered within acceptable standards for consumption according to the RDC Resolution n° 12/2001. In the second period, 100% of the samples obtained in two open markets reached values above the acceptable limit for thermotolerant coliforms and were considered unfit for human consumption. Only samples from one of the open markets were considered acceptable for consumption. Salmonella sp. was negative in all analyzes. CONCLUSION: The results show the necessity for intervention by the competent bodies, organizing actions that promote the marketer awareness that sell food under the terms of the hygiene standards and food handling, thus avoiding damage to the population health.